CLASSIFICATION OF LEXICAL UNITS AND EMOTIVE LEXICON ACCORDING TO GENDER (SCIENCE TIME JOURNAL, 2026)
This article examines the classification of lexical units and emotive lexicon from a gender-based perspective within linguistic and psycholinguistic frameworks. The study analyzes the semantic, pragmatic, and stylistic features of emotive language used by male and female speakers. Special attention is given to positive and negative connotations, evaluative components, and communicative functions of emotive lexical units in relation to gender-specific speech strategies. The research also explores how gender stereotypes and sociocultural factors influence the selection and use of emotionally marked vocabulary. The findings demonstrate that emotive lexicon exhibits gender-based variation and plays a significant role in shaping communication patterns.